Education and Values in Nigeria's National Development (2025)
Societies designed educational processes to propagate their values, traditions and achieve set goals as well as objectives. Several countries particularly, the developing world have found it difficult to achieve this. Achieving society's goals and objectives have been herculean task far Nigeria as a nation. The process of education is established as a veritable tool to correct the anomaly. This paper therefore, examined values that are pertinent to national development, raised questions on the failure of these values far desired growth and attempted answers to the questions. The philosophical research method was employed in the study. The paper concluded that the extinction of African traditional values coupled with economies challenges have contributed to the downturn. The paper recommended the reconsideration of African traditional values and efforts at revamping the economy. This is hoped to go a long way to effect needed growth and developments in Nigeria